Performance of the RACE Score for the Prehospital Identification of Large Vessel Occlusion Stroke in a Suburban/Rural EMS Service. (3rd September 2019) - Dickson, Robert L.; Crowe, Remle P.; Patrick, Casey; Crocker, Kevin; Aiken, Michael; Adams, Andrew; Gleisberg, Guy R.; Nichols, Tyler; Mason, Christopher; Panchal, Ashish R.
Abstract: Introduction : Emergency Medical Services (EMS) providers may identify and preferentially transport patients experiencing large vessel occlusion (LVO) stroke to appropriate treatment centers. The Rapid Arterial oCclusion Evaluation (RACE) scale was created for prehospital LVO detection, yet few studies have evaluated its function in real-world EMS settings. Our objective was to assess the prehospital performance of the RACE scale for detecting LVO stroke following implementation at a large suburban/rural agency in the United States.Methods : In this retrospective analysis, all 9-1-1 patients with an EMS provider primary or secondary impression of stroke treated by the agency between June 1, 2016 and November 1, 2017 were eligible for inclusion. Patient data were abstracted using a standardized form completed by receiving hospitals. Performance for LVO detection at each RACE cutoff value was evaluated using sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). A receiver operating characteristic (ROC) curve was used to evaluate the discrimination of the RACE scale overall. A secondary analysis of RACE for patients experiencing strokes best treated at comprehensive stroke centers (LVO and intracerebral hemorrhage [ICH]) was conducted.Results : There were 440 patients with a documented RACE score and hospital outcome data included in the analysis. About half (51%, n  = 220) were female and the median age was 70 years (IQR: 59–81). Last known well time was under 4.5 hours for 76% of patients ( n  = 261). Over half (61%, n = 269) had a hospital discharge diagnosis of stroke and 64/440 (15%) were classified as LVO. The ROC curve demonstrated adequate discrimination with a c-statistic of 0.72. Performance for identifying LVO in the prehospital setting was greatest for RACE scores ≥5 with a sensitivity of 66% and specificity of 72%, PPV of 29%, and NPV of 93%. A RACE score ≥5 for both LVO and ICH demonstrated sensitivity: 63%, specificity: 77%, PPV: 47% and NPV: 86%.Conclusion : The RACE scale demonstrated acceptable discrimination, yet the sensitivity and positive predictive value were lower in this cohort of EMS professionals in the United States than in the original validation study conducted in Spain. Further work is needed to determine the optimal prehospital screening tool for identification of LVO.